Storage Technology, and Control of Aflatoxin in Corn (Zea mays L.) with Internet of Things (IoT) Application. Issue 1 (July 2021) - Hadipernata, M; Ni'matullah Al-Baarri, A; Somantri, M; Rahayu, E; Munarso, S J; Rachmat, R; Miskiyah,; Misgyarta,; Hayuningtyas, M; Pangidoan, S
Abstract: In the inappropriate storage, corn become a suitable medium for fungus growth. Aspergillus flavus, Aspergillus paraciticus, and Aspergillus nomius produce Aflatoxin that is harmful to humans. One of the problems of Indonesian corn farmer is that storage space does not meet the requirements and corn warehouses still adopt a manually control system. Internet of Thing (IoT) has the potential to be used to facilitate human activities such as transferring and processing data or information through an internet, autonomous, and virtual network. The research objective was to study the corn storage system which has a low aflatoxin content with the IoT Application. The methodology of the study were field observation and desk study related to issues. The results showed that the fungus in corn will grow very fast when the moisture content more than 14 percent. IoT design were be able to maintain moisture content of corn less than 14 percent. IoT system for corn storage consists of room storage, sensors, actuators, monitoring and data storage. Sensor were used for detection and monitoring of the corn condition. The information from this sensor is then processed by a computer program, then the feedback will be done by the actuator.